2022
DOI: 10.1111/josi.12557
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ perceptions and experiences of ageism during the COVID‐19 pandemic

Abstract: The current study investigates older adults’ perceptions of ageism in the United States during the COVID‐19 pandemic. Using tenets of Stereotype Embodiment Theory and the Behaviors from Intergroup Affect and Stereotypes Map framework, we sought to (a) examine whether older adults experienced ageism as self‐relevant during the pandemic and (b) understand whether older adults experienced certain media messages and interpersonal behaviors during the pandemic and interpreted them as being motivated by potentialpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
0
16
1
Order By: Relevance
“…For example, older individuals may be treated as lacking independence and spoken to in oversimplified or patronizing ways (Giles & Ogay, 2007 ; Nelson, 2005 ; Ryan et al., 1995 ). In the context of the pandemic, this may also have included well‐intentioned helping behaviors that signaled to older people that they are dependent and helpless (Derrer‐Merk et al., 2022 ; McDarby et al., 2022 ; Monahan et al., 2020 ; Ng et al., 2022 ). Research has shown that these type of behaviors (i.e., benevolent ageism) negatively affect the health, well‐being and autonomy of older adults (Baltes & Wahl, 1996 ; Cary et al., 2017 ; Derrer‐Merk et al., 2022 ; Langer & Rodin, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, older individuals may be treated as lacking independence and spoken to in oversimplified or patronizing ways (Giles & Ogay, 2007 ; Nelson, 2005 ; Ryan et al., 1995 ). In the context of the pandemic, this may also have included well‐intentioned helping behaviors that signaled to older people that they are dependent and helpless (Derrer‐Merk et al., 2022 ; McDarby et al., 2022 ; Monahan et al., 2020 ; Ng et al., 2022 ). Research has shown that these type of behaviors (i.e., benevolent ageism) negatively affect the health, well‐being and autonomy of older adults (Baltes & Wahl, 1996 ; Cary et al., 2017 ; Derrer‐Merk et al., 2022 ; Langer & Rodin, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary perspective, when faced with the decision of who should get limited medical help, individuals may give preference to younger and healthier individuals because they are more likely to reproduce than older and sicker individuals (Burnstein et al., 1994 ; Duncan & Schaller, 2009 ). Similarly, from a terror management perspective (Greenberg et al., 1986 ), the perceived health threat of COVID‐19 may have increased individuals’ awareness of their own mortality and, thus, led to a desire to distance themselves from older people (Martens et al., 2005 ; McDarby et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…People of older ages are at higher risks of serious illness, hospitalization, and death due to COVID‐19 (Wu et al., 2020 ). Consequently, discourse in the media and public health guidelines have portrayed “the elderly” as a homogenous and highly vulnerable group which requires shielding (Ayalon et al., 2021 ; McDarby et al., 2022 ), while neglecting the role of underlying health conditions and structural determinants of risk such as race, poverty and access to resources (Millett et al., 2020 ; Montero‐Odasso et al., 2020 ). Especially during the early pandemic (spring and summer of 2020), newspapers around the world were fraught with ageist content, ranging from naming the virus “Boomer Remover” to suggesting that older adults should sacrifice themselves for the younger generations and the economy (Ayalon et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the effects of these ageism reduction strategies is an important avenue for future research given the negative health, workplace, psychological, and social consequences of ageism on older adults (Cohn‐Schwartz et al., 2022 ; B. Levy, 2009 ; Levy & Macdonald, 2016 ; McDarby et al., 2022 ). For example, research deriving from stereotype embodiment theory has demonstrated how negative attitudes and stereotypes can have pervasive and insidious effects on the general health and well‐being of older adults (Levy, 2009 ; Chang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the oversimplification of age as a risk factor for COVID‐19 and the framing of older adults as a homogenous vulnerable group reinforces negative views of older adults as burdens (Meisner, 2021 ). In a qualitative analysis of older adults’ experiences during COVID‐19, many reported being aware of the media's framing of older adults as a uniformly frail and vulnerable group (McDarby et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%